Analysis of the implementation of educational supervision by the principal of SMPN 1 Kemuning, Kemuning district, Indragiri Hilir regency - Dedi Surahman; Isjoni; Elfis Suanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
Educational supervision by the school principal is one of the key aspects in maintaining and improving the quality of education in an educational institution. This research aims to (a) analyze the principal's supervision planning for teachers, (b) analyze the implementation of supervision by the school principal towards teachers, (c) analyze the evaluation of supervision by the principal of teachers, and (d) analyzing the follow-up supervision by the principal of teachers at SMPN 1 Kemuning, Kemuning district, Indragiri Hilir regency. This research was conducted using a qualitative approach with descriptive qualitative research methods. The research informants consisted of (a) the principal of SMP Negeri 1 Kemuning, Indragiri Hilir regency as a key informant or core informant; (b) an educational assistant at SMP Negeri 1 Kemuning, Indragiri Hilir Regency as a key informant or core informant; and (c) teachers at SMP Negeri 1 Kemuning, Indragiri Hilir regency as control informants. Data collection techniques consist of observation and interviews. The research instruments used were observation sheets and interview lists. The data analysis technique in this research uses the Spradley model. The validity of the data in this research was carried out by source and time triangulation. The research results can be concluded that there are four stages in implementing supervision, namely that supervision planning has not been implemented optimally because the supervision time has not been maximized and the instruments to be used have not met supervision needs. Furthermore, the implementation of supervision by the teachers' principal at SMPN 1 Kemuning, Kemuning district, Indragiri Hilir regency, has gone well.